2020
DOI: 10.1017/cts.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

A call to action to address rural mental health disparities

Abstract: Rural residents in the USA experience significant disparities in mental health outcomes even though the prevalence of mental illness in rural and metropolitan areas is similar. This is a persistent problem that requires innovative approaches to resolve. Adopting and appropriately modifying the National Institute on Minority Health and Health Disparities research framework are the potential approaches to understanding how these disparities might be addressed through research. Using this research framework can f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(190 citation statements)
references
References 39 publications
6
148
0
Order By: Relevance
“…A study found that there used to be a treatment disparity between rural and urban settings when it comes to provision of mental health services (Morales et al, 2020). Individuals living in rural area tend to receive mental health check-ups and treatments less frequently that too from less trained personnel mostly (Morales et al, 2020).…”
Section: Relationship Between Schizophrenia Related Variables Of the ...mentioning
confidence: 99%
“…A study found that there used to be a treatment disparity between rural and urban settings when it comes to provision of mental health services (Morales et al, 2020). Individuals living in rural area tend to receive mental health check-ups and treatments less frequently that too from less trained personnel mostly (Morales et al, 2020).…”
Section: Relationship Between Schizophrenia Related Variables Of the ...mentioning
confidence: 99%
“…Adults residing in rural geographic locations may receive mental health treatment less frequently, often with providers with less specialized training compared to those residing in metropolitan locations [22]. The reasons underlying this mental health treatment disparity include paucity of mental health services, reduced access and underutilization of available services, and professional staffing shortages [22]. The utilization of mental health services is affected by distance as well; the longer the distance, the less the service is used [23].…”
Section: The Case Of Rural Areasmentioning
confidence: 99%
“…Recent research has suggested that patients with medical conditions such as heart disease or traumatic brain injury residing in rural areas were less likely to utilize specialized services and were in risk for worse outcomes, compared to urban patients (Brown et al, 2019; Field et al, 2018; Yue et al, 2020). Similarly, it has been shown that patients residing in rural geographic locations receive mental health treatment less frequently and often by professionals with less specialized training, when compared to those residing in metropolitan locations (Morales et al, 2020). The reasons underlying this mental health treatment disparity are well documented and include reduced access to services and limited availability of specialty mental health care in rural areas; lack of trained mental health personnel and care coordination in rural medical care; mental health staff shortages; and underutilization of available services (Morales et al, 2020; Thornicroft et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been shown that patients residing in rural geographic locations receive mental health treatment less frequently and often by professionals with less specialized training, when compared to those residing in metropolitan locations (Morales et al, 2020). The reasons underlying this mental health treatment disparity are well documented and include reduced access to services and limited availability of specialty mental health care in rural areas; lack of trained mental health personnel and care coordination in rural medical care; mental health staff shortages; and underutilization of available services (Morales et al, 2020; Thornicroft et al, 2011). Family structure and socioeconomic status are also involved in mental health care utilization (Hauenstein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%